Optimizing Adaptive Governance as a Solution for Food Self-Sufficiency and Family Resilience in Makassar City - Iin Ismayanti; Beddu Lahi (Universitas Pancasakti, 2026)
The urgency of this study lies in the decline of agricultural land area in Makassar City by 600 hectares over the past decade, and the city's Food Security Index (FSI) ranking of 54th nationally with a score of 87.95, indicating significant challenges to food self-sufficiency. Consequently, an adaptive governance strategy is needed to enhance local food production, improve distribution systems, and ensure stable food access for the population. This study aims to explore the role of adaptive governance in enhancing the effectiveness of food self-sufficiency policy and in strengthening family resilience in Makassar City. A qualitative research approach was employed, with data collected through interviews, observation, documentation, and focus group discussions (FGDs). Data were analyzed using NVivo 12 Plus. The findings confirm that food self-sufficiency efforts in Makassar City continue to be constrained by agricultural land depletion, weak distribution infrastructure, high logistical costs, low community participation, and institutional fragmentation, compounded by external factors such as climate change and global price fluctuations. To address these challenges, an adaptive governance approach is required through data-driven institutional capacity building, multi-stakeholder collaboration, utilization of social capital, agricultural technology innovation, and policy flexibility. Through these strategies, Makassar has the potential to develop a resilient, inclusive, and sustainable food system, while serving as a model for adaptive food governance in Indonesia.